1991
DOI: 10.1136/adc.66.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding and protection against neonatal sepsis in a high risk population.

Abstract: Protection against neonatal sepsis by breast feeding was investigated in a developing community. A case-control study was carried out with 42 cases from a hospital and 270 controls, matched for age and socioeconomic conditions from the community. Exclusive breast feeding was extremely rare, most babies being partially breast fed and a few being given formula feed or animal milk.A highly significant odds ratio of 18 was obtained, showing that even partial breast feeding protects against neonatal sepsis in such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 6 publications
1
59
1
3
Order By: Relevance
“…and Camp.vlohacter (4) is related to the specific SIgA antibody levels in the mother's milk. The relevance of milk-mediated protection may be illustrated by the fact that breast-feeding shows a striking protection against the two infections that are among the most common causes of death in early life in a poor community: diarrhea and neonatal septicemia (3,39).…”
Section: Discussionmentioning
confidence: 99%
“…and Camp.vlohacter (4) is related to the specific SIgA antibody levels in the mother's milk. The relevance of milk-mediated protection may be illustrated by the fact that breast-feeding shows a striking protection against the two infections that are among the most common causes of death in early life in a poor community: diarrhea and neonatal septicemia (3,39).…”
Section: Discussionmentioning
confidence: 99%
“…There is also additional evidence linking lack of exclusive breastfeeding with increased risk of earlyonset 520 and late-onset neonatal sepsis. 521 community-based evidence. Our review identified several studies that addressed the issue of impact of breastfeeding practices on perinatal and neonatal outcomes in developing countries.…”
Section: Breastfeedingmentioning
confidence: 99%
“…Breast-feeding has been associated with lower rates of a variety of infant illness, such as necrotizing enterocolitis (22), sepsis (23), and respiratory illness (24). In fact, breast milk contains a number of bioactive substances, including enzymes, growth factors, and hormones (25).…”
Section: Discussionmentioning
confidence: 99%